Perancangan Mesin Filtrasi Minyak Jelantah Portable dengan Metode Ergonomi Partisipatori - Saputri, Anggraini Dwi; Adi Kuncoro, Danang; Amalia Pratiwi, Rizki; Andriyas Puji, Ari (SURYA TEKNIKA, 2025)
This study is motivated by the high consumption of cooking oil in the Micro, Small, and Medium Enterprises (MSMEs) sector, which is often constrained by operational costs, triggering the repeated use of waste cooking oil (jelantah) that poses carcinogenic health risks. This study aims to design and build a portable waste cooking oil filtration machine for households/MSMEs to provide a preventive solution to health risks while supporting economic efficiency. The research method uses a Participatory Ergonomics approach, involving active stakeholder participation including users, chemists, and manufacturing practitioners in identifying design needs. The design development results transformed the initial concept relying solely on gravity into an integrated four-stage purification system, namely: initial filtration using 100 mesh, heating process to reduce viscosity, water and odor absorption using zeolite adsorbent, and final filtration. The realization of the prototype with dimensions of 36 × 35 × 67 cm shows that this system is effective in separating solid contaminants, reducing water content and rancid odor, and producing visually clearer and usable oil. However, this study is limited to qualitative evaluation of oil clarity, odor, and water content reduction, and has not yet included quantitative laboratory analysis of free fatty acid levels.